Pendekatan Islam terhadap Keadilan Sosial - Qutb, Syed (Unisia, 2016)
The spirit and vision of Islam compriese whole aspects of life. These make Islamic faith capable of creating balances and equalities inasociety. Justice from perspective of Islam has differed crealy from that narrowly perceived by comunism. Justice in Islam, according to the.writer, absolutely requires eqalities of people which, at the same time, show the whole values. This writing reviews justice consepts deeply, both ingiving opportunities and freedom.